Experiências de casais com parto domiciliar: da escolha à vivência - Hiene, Rafaela Roque Siani (Universidade Federal de São Carlos, 2018)
During the sixteenth century, the act of giving birth was understood as being essentialy female; that is, women were responsible for providing emotional support to other women, helping them to give birth in their own homes. Community traditional midwives provided intrapartum care for women who lived around them. Over the years and the technological development, this scenario was gradually switched towards the biomedical model of health care, by which childbirth was considered a disease to be treated in the hospital. Thanks to the movement of humanization of childbirth care though, home is currently considered a safe birthplace choice, since it is assisted by a qualified intrapartum care team. In this medicalization of childbirth context, couples who decide to live this experience face several difficulties throughout the pregnancy and childbirth period. Thus, this study aims to understand the elements which assiste dor hindered the couples’ path and experience with home birth. This is a multiple cases study that presents a qualitative approach. Data collection tool was driven by the principles of Communicative Methodology, which is based on egalitarian dialogue and, therefore, recognizes the different contributions of the subjects depending on their arguments validity, instead of valuing them from the perspective of each one’s dominance positions. Data collection was performed through a communicative account - a particular type of face-to-face interview where analysis is performed together with the study participants. Data analysis was guided by the Content Analysis Method, that generated the following categories: "Escaping the current model of intrapartum care", "Negative family experiences with normal childbirth", "Information-seeking movement and empowerment" and "Received support (or the lack of it) from family and friends". Our results indicate that the lack of support from family and friends in the decision of home birth, as well as negative family experiences with labour and delivery, were aspects that hindered these couples trajectory. Information and empowerment sources, however, as well the team being respectfull in terms of woman autonomy, represented positive factors which brought fulfillment with the lived experience. All couples mentioned home birth as a way of escaping the conventional system of intrapartum care that currently rules most hospitals protocols, and it was also observed that home birth does not assure 100 % of couples satisfaction and autonomy. We concluded that all interviewed couples decided for home birth after deep thought and seek for information. They also considered these experiences to be well succeeded, valuing elements such as autonomy of decisions, respect of the involved team, and impressions of greater belonging and involvement with the whole process. Finally, it is noteworthy the continuing need for communication improvement between intrapartum team and family members during labour and delivery, an important finding pointed out by couples as disruptive when the team was not alert to it.
Couples experiences with home childbirth: from choice to the actual event
Keywords: Parto humanizado; Acontecimentos que mudam a vida; Parto domiciliar; Família; Humanizing childbirth; Life change events; Home childbirth; Family; CIENCIAS DA SAUDE::ENFERMAGEM